The Influence of Teaching Personnel Empowerment, Madrasah Commitment and Culture of Innovation on Madrasah Effectiveness - Mirawati; Ali, Hapzi; Imron Rosadi, Kemas (International Journal of Advanced Multidisciplinary, 2023)
The Influence of Teaching Personnel Empowerment, Madrasah Commitment and Innovation Culture on Madrasah Effectiveness is a scientific article of literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Empowerment of Education Personnel influences Madrasah Effectiveness; 2) Madrasah Commitment influences Madrasah Effectiveness; and 3) Innovation Culture influences Madrasah Effectiveness.